2016
DOI: 10.1371/journal.pmed.1002103
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes Associated with Traumatic Brain Injury in Childhood and Adolescence: A Nationwide Swedish Cohort Study of a Wide Range of Medical and Social Outcomes

Abstract: BackgroundTraumatic brain injury (TBI) is the leading cause of disability and mortality in children and young adults worldwide. It remains unclear, however, how TBI in childhood and adolescence is associated with adult mortality, psychiatric morbidity, and social outcomes.Methods and FindingsIn a Swedish birth cohort between 1973 and 1985 of 1,143,470 individuals, we identified all those who had sustained at least one TBI (n = 104,290 or 9.1%) up to age 25 y and their unaffected siblings (n = 68,268) using pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
176
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 219 publications
(188 citation statements)
references
References 52 publications
12
176
0
Order By: Relevance
“…Neuro developmental disability is also a risk factor for other health difficulties, including selfharm and substance misuse. 147 Bespoke interventions supporting developmental needs that are well evidenced in other settings should also be employed within criminal justice settings such as adolescent detention facilities. 3 Detention provides an opportunity to initiate treatment for myriad health conditions, such as catchup vaccinations to protect against HBV.…”
Section: Scoping Reviewmentioning
confidence: 99%
“…Neuro developmental disability is also a risk factor for other health difficulties, including selfharm and substance misuse. 147 Bespoke interventions supporting developmental needs that are well evidenced in other settings should also be employed within criminal justice settings such as adolescent detention facilities. 3 Detention provides an opportunity to initiate treatment for myriad health conditions, such as catchup vaccinations to protect against HBV.…”
Section: Scoping Reviewmentioning
confidence: 99%
“…A Swedish study of over a million individuals under the age of 26 years identified 104 290 with a prior traumatic brain injury (TBI). Compared with their unaffected siblings, those with mild TBI (concussion) were more likely to be in receipt of a disability pension or welfare payments, to have had more psychiatric inpatient admissions or outpatient visits, to die younger and to have lower educational achievement (p<0.05 for all) 22. A recent study of 294 paediatric sports-related concussion patients in the USA found that girls were three or four times more likely to experience postconcussive symptoms lasting >28 days than boys,23 a particular concern given the Rugby Unions’ focus on increasing the number of female rugby players 24.…”
Section: Introductionmentioning
confidence: 99%
“…Since those systematic reviews were published, Sariaslan et al 28 published a detailed examination of outcomes of brain injury using Swedish population data. They found convincing evidence that moderate to severe brain injury in childhood and adolescence was associated with an increased rate of psychiatric disorder and receipt of health-related disability benefits in adult life.…”
Section: A Little Less Conversation a Little More Science Pleasementioning
confidence: 99%